Towards a contextual understanding of public intellectuals : assessing Thabo Mbeki against Edward Said’s characterisation of intellectuals within a South African context - Thuynsma, Heather Anne (University of Pretoria, 2022)
Dissertation( MA (Political Sciences))--University of Pretoria, 2021.